Penerapan Tata Kelola Lingkungan dalam Pengelolaan Ruang Terbuka Hijau (RTH) di Kabupaten Ponorogo - Yhoga Hardy Wiratama; Wawan Sobari; Ali Mashuri (Brawijaya Journal of Social Science, 2023)
Public awareness arises by building green open spaces (RTH) which are used as facilities to improve environmental quality. Effective environmental governance involves awareness, empowerment, coordination and enforcement between government, communities and the private sector. In this study researchers used qualitative methods. The use of qualitative methods is used to understand the phenomena that occur in research. By using qualitative methods, you can explore data in depth so that data collection and data analysis produce accurate data for drawing conclusions. This qualitative case study aims to explore the workings of implementing environmental governance in the management of green open spaces. Data collection techniques used are observation, interviews and documentation. The results of this study indicate that the use of the concept of environmental governance in this study is in the management of green open spaces in Ponorogo seen from the theory of awareness, empowerment, coordination and enforcement which expands on the theory from previous studies. The management of green open space which involves many public actors, namely the government, non-governmental organizations, the private sector and the community will certainly assist the local government in managing it. In this case the effectiveness of environmental governance in the efforts of the Ponorogo Regency Government has been implemented well because it has given awareness to the community of green open spaces provided and the public cares about green open spaces as lungs that can be preserved.